The Influence of Work Discipline, Job Satisfaction, and Performance Supervision of Work Employees at PT Makmur Abadi Raya - Melkyory Andronicus; Johansen; Michael Lim Vinci; Andrea Sadeli (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this study is to examine and analyze the effect of Work Discipline, Job Satisfaction and Work Supervision on employee performance at PT Makmur Abadi Raya. Low employee performance can be seen from not achieving the company's targets due to low work discipline, low job satisfaction and supervision that has not gone well. The population and sample in this study amounted to 63 employees. The research method uses multiple linear regression analysis techniques. The calculation result of hypothesis testing is partially obtained tcount> ttable or 2,875> 2,001 and significantly obtained 0.006 <0.05, meaning that partially Work Discipline has a positive and significant effect on employee performance at PT Makmur Abadi Raya. The results of calculation of hypothesis testing partially obtained tcount> ttable or 2.024> 2.001 and obtained significant 0.048 <0.05, meaning partially Job Satisfaction has a positive and significant effect on employee performance at PT Makmur Abadi Raya. The results of the calculation of the partial hypothesis testing obtained tcount> ttable or 2.006> 2.001 and the significant value obtained was 0.049 <0.05, meaning that partially Work Supervision has a positive and significant effect on employee performance at PT Makmur Abadi Raya. The test results obtained by the value of F count (11.051)> F table (2.76) and a significance probability of 0.000 <0.05, meaning that Ho is rejected and Ha is accepted, namely that simultaneously Work Discipline, Job Satisfaction and Work Supervision have a positive and significant effect on performance. employees at PT Makmur Abadi Raya. The conclusions in this study indicate that partially and simultaneously Work Discipline, Job Satisfaction and Work Supervision have a positive and significant effect on employee performance at PT Makmur Abadi Raya.